NARRATIVE STRATEGY AND THEATRICAL CREATIVITY IN PAK NASIR'S SITA MARRIAGE CONTEST - Widagdo, Bimo Sinung; Darmoko, Darmoko (International Review of Humanities Studies, 2023)
Shadow puppets are very popular in Southeast Asia. The foreign culture that is present in this area has a strong enough influence on the growth and existence of local culture. Stories were brought and spread by the Indians at the beginning of the Christian era as material developed through their local intelligence. Two geographical areas that are unique in Malay culture are important and deserve attention, namely Malaysia and Thailand. Kelantan Malay shadow puppets cannot be separated from the influences inherent in them, namely Java and Thailand. The plays that are shown revolve around Rama's struggle to get Sita, who is assisted by his younger brother, Laksmana. Nasir's play Sita's Mariage Contest deserves to be appointed as an object of study on the grounds that the mythical and magical content is very strong and Malay local wisdom is in contact with Javanese and Pattani localities in Thailand. The data is downloaded from https://www.youtube.com/watch?v= DbA53E3M0Zw. To examine the data, a qualitative descriptive method is needed, as well as a theoretical framework of narrative strategies, namely sanggit play and work on pakliran. The results of the study show that sanggit play, which is the power of knowledge of the dalang, is packed with mythical and magical content and combines genealogy, tradition, and local conventions of Malay (Malaysia), Javanese (Indonesian), and Pattani (Thailand) armed with the power of imagination, intuition, sensitivity, intellectuality, and mastery of cultural codes. The work on pakliran combines ethics and aesthetics that describe local wisdom with the implementation of acculturation and adaptation as a Malay cultural identity.